Relative aerobic and anaerobic energy contributions during short-duration exercise remain unchanged over a wide range of exercise intensities - Shiraki, S.; Fujii, N.; Yamamoto, K.; Ogata, M.; Kigoshi, K. (International Journal of Sport & Health Science, 2020)
The present study aimed to examine whether different exercise intensities, ranging from submaximal to supramaximal, modulate the relative contributions of aerobic and anaerobic energy systems during short-duration exercise. Eight competitive male track and field athletes (22.3 ± 1.0 years) performed a 30-s pedaling test at seven different intensities corresponding to O2 demands of 40, 50, 60, 70, 80, 90, and 100 ml/kg/min. The power outputs required at each O2 demand were determined from the extrapolated linear relationships between power and the steady-state O2 uptake obtained during submaximal-intensity exercise. The VO2max test and 30-s Wingate anaerobic test were also performed. Relative aerobic and anaerobic energy contributions were estimated by the ratio of O2 uptake and O2 deficit, the latter being calculated as the difference between O2 demand and O2 uptake. The exercise intensity of the 30-s pedaling test ranged from 73.4 ± 7.4 to 180.9 ± 18.2% VO2max. As exercise intensity increased, O2 uptake (13.9 ± 2.1 to 26.8 ± 2.1 ml/kg/min) and O2 deficit (26.9 ± 2.1 to 73.7 ± 2.2 ml/kg/min) during the 30-s pedaling test increased (P < 0.05). However, the relative aerobic (34.1 ± 5.1 to 26.7 ± 2.0%) and anaerobic (65.9 ± 5.1 to 73.3 ± 2.0%) energy contributions during the 30-s pedaling test did not differ across all O2 demands (P > 0.05). These results suggest that the relative aerobic and anaerobic energy contributions during short-duration exercise remain nearly constant over a wide range of exercise intensity.